Menguasai Labirin Keuangan dan Sumber Daya Manusia di Industri Minyak dan Gas: Pengalaman Magang di PT. Indosino Oil & Gas - Christopher Halomoan (Ethics and Law Journal: Business and Notary, 2024)
This study aims to analyze the practical integration of finance and human resources (HR) theories into the real-world operations of PT. Indosino Oil & Gas, an oil and gas company in Indonesia. The internship program spanned six months, from March 2024 to August 2024, and involved active participation in the company's finance and HR divisions. The research focuses on identifying the challenges encountered in the implementation of finance and HR practices within the dynamic oil and gas industry and the solutions implemented by PT. Indosino Oil & Gas. Additionally, the study explores the role of technology in facilitating financial and HR management and the impact of the internship experience on the professional development of students. Data were collected through direct observation, document analysis, and literature review. The findings reveal the significant contribution of advanced technologies in enhancing data accuracy and operational efficiency, as well as the importance of comprehensive mentorship in preparing students for careers in the oil and gas sector.. Abstrak Penelitian ini bertujuan untuk menganalisis integrasi praktis teori keuangan dan sumber daya manusia (SDM) ke dalam operasi nyata PT. Indosino Oil & Gas, sebuah perusahaan minyak dan gas di Indonesia. Program magang berlangsung selama enam bulan, dari Maret 2024 hingga Agustus 2024, dengan partisipasi aktif dalam divisi keuangan dan SDM perusahaan. Penelitian ini berfokus pada identifikasi tantangan yang dihadapi dalam penerapan praktik keuangan dan SDM dalam industri minyak dan gas yang dinamis serta solusi yang diimplementasikan oleh PT. Indosino Oil & Gas. Selain itu, penelitian ini mengeksplorasi peran teknologi dalam mempermudah pengelolaan keuangan dan SDM serta dampak pengalaman magang terhadap pengembangan profesional mahasiswa. Data dikumpulkan melalui observasi langsung, analisis dokumen, dan tinjauan literatur. Temuan mengungkapkan kontribusi signifikan teknologi canggih dalam meningkatkan akurasi data dan efisiensi operasional, serta pentingnya bimbingan yang komprehensif dalam mempersiapkan mahasiswa untuk karir di sektor minyak dan gas. Kata kunci: Keuangan, Sumber Daya Manusia, Minyak dan Gas, Magang, Teknologi